Uji Efektivitas Berbagai Konsentrasi Pestisida Nabati Bintaro (Cerbera manghas) terhadap Hama Ulat Grayak (Spodoptera litura) pada Tanaman Kedelai - Setiawan, Agus Nugroho; Supriyadi, Achmad (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
Spodoptera litura is a major pest in soybean cultivation causing damage by 80%. One of control is done  by using bintaro plants (Cerbera manghas) potential as a botanical pesticide (insecticide). This study aims to determine the effectiveness of botanical pesticide from bintaro extract and get the precise extract concentration of fruit, young leaves, and old leaves of bintaro to control Spodoptera litura on soybean plants, and its influence to  the growth of soybean plants. This study used an experimental method that is designed in a single factor completely randomized design using pesticides Bintaro (young leaves, old leaves, and fruit), which consists of three concentrations (100 g / l, 200 g / l, and 300 g / l), add two treatments, namely, sprayed with water and a  synthetic pesticides as a control. Result showed the leaves and fruit of Bintaro at concentrations of 100 g/ l to 300 g/ l by solvent extraction has not been effectively used as botanical pesticide to control Spodoptera litura on soybean plants. Old leaf Bintaro extract (100 g/ l) produces highest pest mortality value and  rate of 40.00% and 2.00. The use of botanical pesticide from extract bintaro (fruit and leaf) is not inhibit the growth of soybean plants.